Orientalis Dan Tantangan Terhadap Integritas Alquran - Masruchin Masruchin; Muhammad Adil Rifahi; Muhammad Kholiluddin (Al-Wajih: The Journal of Islamic Studies, 2025)
The study of the Qur'ān is not only conducted by Muslim scholars, but also by Western scholars known as orientalists. This study aims to critically analyze the challenges posed by orientalists to the integrity of the Qur'ān, focusing on four main issues: claims of influence from previous religious texts, the Qur'ānic codification process, variations in recitation (qira'at), and the authenticity of language and text structure. The method used in this research is a qualitative study with a literature approach, namely through a critical review of the works of orientalist figures such as Abraham Geiger, John Wansbrough, Richard Bell, and Arthur Jeffery, as well as comparisons from the views of Muslim scholars such as M.M. Al-Azami and Toshihiko Jeffery. Al-Azami and Toshihiko Izutsu. The results show that although orientalists have contributed to opening up a space for academic dialogue about the Qur'ān, many of their claims contain methodological biases and historical assumptions that do not consider the context of Islamic revelation. On the other hand, Islamic scholarly tradition shows that the Qur'ān has undergone a systematic codification process since the time of the Prophet Muhammad, and that variations in recitation (qira'at) are part of the linguistic richness that remains within the framework of Islamic orthodoxy.